Композити поліпропілен – вуглецеві нанотрубки: структурні особливості, фізико-хімічні властивості - Sementsov, Yu. I.; Prikhodko, G. P.; Kartel, N. T.; Mahno, S. M.; Grabovsky, Yu. E.; Aleksyeyev, O. M.; Pinchuk-Rugal, T. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
Polypropylene-carbon nanotubes composites were obtained. The features of structure, melting and crystallization as well as the mechanical, elektro- and thermophysical properties of the composites were investigated. It is shown that an incorporation of small amount of carbon nanotubes in the polypropylene matrix causes to an unmonotonous change of the matrix cristallinity which, in turn, has an influence of the change of physical properties of the composites. The formation of continuous net of carbon nanotubes into the polypropylene matrix leads to the substantial growth of tensile strength on compression; the diminishing of deformation of destruction; the increase of conductivity almost in five orders at the insignificant increase of heat conductivity.